Female infertility and diet, is there a role for a personalized nutritional approach in assisted reproductive technologies? A Narrative Review - Kohil, Amira; Chouliaras, Spyridon; Alabduljabbar, Shaikha; Lakshmanan, Arun Prasath; Ahmed, Salma Hayder; Awwad, Johnny; Terranegra, Annalisa (Frontiers in Nutrition, 2022)
Female infertility is a major public health concern and a global challenge. It is a disorder of the reproductive system, defined as the inability to achieve a clinical pregnancy. Nutrition and other environmental factors are found to impact reproductive health in women as well as the outcome of assisted reproductive technologies (ART). Dietary factors, such as polyunsaturated fatty acids (PUFA), fiber as well as the intake of Mediterranean diet appear to exert beneficial effects on female reproductive outcomes. The exact mechanisms associating diet to female fertility are yet to be identified, although genomic, epigenomic and microbial pathways may be implicated. This review aims to summarize the current knowledge on the impact of dietary components on female reproduction and ART outcomes, and to discuss the relevant interplay of diet with genome, epigenome and microbial composition.